Epidemiological analysis of septic shock in the plateau region of China - Li, Qianwei; Chai, Wenzhao; Wang, Xiaoting; Cheng, Li; Cai, Xin; Fu, Jianlei; Pan, Wenjun; Lin, Guoying (Frontiers in Medicine, 2022)
Purpose: Little epidemiological data exist on patients with severe infection in the plateau region of China, and the data that do exist are lacking in quality. Using the medical records of patients with severe infection in the Department of Intensive Medicine (intensive care unit; ICU) of the People’s Hospital of Tibet Autonomous Region, this study analyzed the epidemiological and clinical characteristics of patients with septic shock in plateau area (Tibet), with the ultimate aim of reducing the incidence and mortality from this condition. Methods: Clinical data on 137 patients with septic shock in the studied ICU from November 2017 to October 2019 were retrospectively analyzed using SPSS, Version 21.0. Results: Among the 137 patients with septic shock, there were 47 survivors and 90 in-hospital or post-discharge deaths. There were 91 male patients and 46 female patients. The incidence of septic shock was 11.3%, and mortality rate was 65.7%. Median age was 55 years old, median APACHE-II score on the day of admission was 17, median SOFA score was 11, and median number of organ injuries was one. APACHE-II score (P = 0.02), SOFA score (P < .001), and the number of organ injuries (P < 0.001) were higher among patients who died than among survivors. The infections were mainly pulmonary and abdominal, and the main pathogen was gram-negative bacteria. Conclusion: The incidence and mortality of septic shock in ICU wards in Tibet are very high. The APACHE-II score, SOFA score, and the number of organ damage on the first day after diagnosis are independent risk factors for septic shock. To some extent, this study reflects the epidemiological characteristics of septic shock in the plateau region of China (≥ 3650 m above sea level) and provides data that can support the prevention and treatment of sepsis in the future. More and deeper epidemiological studies of septic shock are necessary.